Semi-automated updating of polygon boundaries in the Forest Map of Spain - Castilla, G. (Forest Systems, 2006)
The principles of the future European Directive on Spatial Data Infrastructures inspire the new Spanish Information System on Land Occupation (SIOSE), where the information from the various existing landcover/landuse maps will be integrated, including that of the Forest Map of Spain (MFE). This work describes a test commissioned by the Nature Database Department of the Ministry of Environment, whose goal is to evaluate the possibility of semiautomatic updating, by means of an image segmentation algorithm developed by the author, of MFE polygon edges. The updated map may be used later to represent forest areas in SIOSE. The result, although needs to be confirmed by further tests, is very positive, because more than 80% of the edges of the final map come from the automatic segmentation, which may represent more than a 40% time-saving in the photointerpretation.